Ecological trends in Green Economy transition in industrial region - Dvinin Dmitry; Pletnev Dmitri; Zabelina Ekaterina (BIO Web of Conferences)
The article is devoted to the assessment of the achievement of existing global environmental trends related to the transition to a green economy using the example of an industrial region. The main trends in greening the regional economy are selected and assessed. It is established that the implementation of environmental trends in the Chelyabinsk region is very heterogeneous. The highest score was given to the trend related to the overall reduction of emissions into the atmosphere, which is explained by the implementation of comprehensive regional programs that made it possible to reduce the emission of pollutants. It was revealed that the situation is slightly worse with the transition to environmentally friendly transport, in the field of waste management and disposal and the preservation of natural ecosystems. The region has some achievements in this area, but they cannot be compared with the best world practices. It is noted that the region almost completely lacks activities to develop low- carbon energy and achieve carbon neutrality, green construction and greening of agriculture. These environmental trends can be taken into account in further adjustment of the environmental policy of the Chelyabinsk region.